2023
DOI: 10.3389/fpls.2022.1035906
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis of important agronomic traits and metabolites in foxtail millet (Setaria italica) by RIL population and widely targeted metabolome

Abstract: As a bridge between genome and phenotype, metabolome is closely related to plant growth and development. However, the research on the combination of genome, metabolome and multiple agronomic traits in foxtail millet (Setaria italica) is insufficient. Here, based on the linkage analysis of 3,452 metabolites via with high-quality genetic linkage maps, we detected a total of 1,049 metabolic quantitative trait loci (mQTLs) distributed in 11 hotspots, and 28 metabolite-related candidate genes were mined from 14 mQT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The distribution of qualitative traits shows the occurrence of six panicle shapes (cylindrical, conical, spindle, club, candle, and lanceolate). When examining unique features, the candle shape exhibited the highest number (58), followed by lanceolate (37), cylindrical (29), club (14), conical (10), and spindle (10) (Fig. 4b).…”
Section: Selection Distribution and Classi Cation Of The Top Metaboli...mentioning
confidence: 99%
See 3 more Smart Citations
“…The distribution of qualitative traits shows the occurrence of six panicle shapes (cylindrical, conical, spindle, club, candle, and lanceolate). When examining unique features, the candle shape exhibited the highest number (58), followed by lanceolate (37), cylindrical (29), club (14), conical (10), and spindle (10) (Fig. 4b).…”
Section: Selection Distribution and Classi Cation Of The Top Metaboli...mentioning
confidence: 99%
“…The grains were categorized into seven colour classes. Among these, genotypes with gray grain colour showed the highest number of unique metabolic markers (52), followed by brown-gray (42), a mixture of yellow and gray grains (29), deep gray (17), yellow (11), brown (10), and cream (7) (Fig. 4h).…”
Section: Selection Distribution and Classi Cation Of The Top Metaboli...mentioning
confidence: 99%
See 2 more Smart Citations
“…Grain yield is one of the most important traits in cereals. A QTL analysis using RIL population of foxtail millet conducted by Wei et al (2022) identified a potential yield-related gene, Si035172m. The Si035172m homologous gene in rice, OsTE, is a co-activator of APC/C.…”
Section: Mean Value and Standard Deviation Of Iceri-5 Botok-10 And F2...mentioning
confidence: 99%